Идентификация термонапряженного состояния составного цилиндра - Сергиенко, И.В.; Дейнека, В.С. (Проблемы управления и информатики, 2009)
Представлено явні вирази градієнтів функціоналів-нев’язок для ідентифікації градієнтними методами різноманітних параметрів задач термонапруженого деформування складеного кругового циліндра. The explicit expressions of functionals-residuals gradients for identification of various parameters in thermostressed deformation of compound circular cylinder problems by means of gradient methods are presented.